Effect of the peak temperatures and of the cooling rate on the damping properties of manganese-copper base alloys - Chaikovskii, B.S.; Yaroslavskii, G.Ya.; Bocharova, L.A. (Проблемы прочности, 1985)
We investigated alloys differing in chemical composition as well as by the regimes of heat treatment in the initial state (before heat cycling). Heat cycling consisted in heating blanks of a copper-manganese alloy to 200-850° C with subsequent cooling at rates of 5 to 150-200° C/sec. After the heat cycling, specimens for investigating the damping properties were made from the blanks.